Bioinspired Hierarchical Nanofibrous Silver-Nanoparticle/Anatase-Rutile-Titania Composite as an Anode Material for Lithium-Ion Batteries - Luo, Yan (Langmuir : the ACS journal of surfaces and colloids, 2016)
A new bioinspired hierarchical nanofibrous silver-nanoparticle/anatase-rutile-titania (Ag-NP/A-R-titania) composite was fabricated by employing a natural cellulose substance (e.g., commercial laboratory cellulose filter paper) as the structural scaffold template, which was composed of anatase-phase titania (A-titania) nanotubes with rutile-phase titania (R-titania) nanoneedles grown on the surfaces and further silver nanoparticles (AgNPs) immobilized thereon. As it was employed as an anode material for lithium-ion batteries (LIBs), high reversible capacity, enhanced rate performance, and excellent cycling stability were achieved as compared with those of the corresponding cellulose-substance-derived nanotubular A-titania, R-titania, heterogeneous anatase/rutile titania (A-R-titania) composite, and commercial P25 powder. This benefited from its unique porous cross-linked three-dimensional structure inherited from the initial cellulose substance scaffold, which enhances the sufficient electrode/electrolyte contact, relieves the severe volume change upon cycling, and improves the amount of lithium-ion storage; moreover, the high loading content of the silver component in the composite improves the electrical conductivity of the electrode. The structural integrity of the composite was maintained upon long-term charge/discharge cycling, indicating its significant stability